Barriers and enablers to exclusive breastfeeding by mothers in Polokwane, South Africa - Makwela, Maishataba Solomon; Mashaba, Reneilwe Given; Ntimana, Cairo Bruce; Seakamela, Kagiso Peace; Maimela, Eric (Frontiers in Global Women's Health, 2024)
Background: Exclusive breastfeeding (EBF) for six months, with the introduction of appropriate complementary feeding thereafter, and breastfeeding continuing for up to 2 years and beyond, is highly recommended. This could save the lives of up to 1.4 million children each year worldwide. Despite this, breastfeeding rates in South Africa remain sub-optimal, with the recommended target of 50% by the World Health Assembly (WHA) not being achieved. The study aimed to investigate the reasons influencing mothers' practice of exclusive breastfeeding in the Polokwane municipality of Limpopo province in South Africa. Methodology: A cross-sectional health facility-based quantitative and descriptive survey was conducted using a validated-structured questionnaire administered to 146 mothers. The data was analyzed using STATA. Chi-square tests were used to determine the relationship between selected demographic variables and their reasons not to breastfeed exclusively. Results: Although 94% of the mothers had initiated breastfeeding, at the time of data collection 8% had stopped. Of those who had stopped breastfeeding, 5% did so within one month of starting. Thirty- nine percent of mothers’ breastfed exclusively, while 61% practiced mixed feeding. A positive association between exclusive breastfeeding practices and the age of the mother were observed, with older mothers more likely to breastfeed. The reasons mothers stopped breastfeeding were: the mother was ill (45%) or they returned to school or work (27%). Reasons for not breastfeeding were cited as: medical conditions, not enough milk, and infant refusal to breastfeed (33%). Mothers believe that HIV-positive women should breastfeed their infants (57%), and health workers were found to be the main source of HIV information to mothers (77%). Conclusions: Exclusive breastfeeding during the first six months was less practiced. Infant formula and solid foods were introduced at an early age, usually within the first month of breastfeeding. This study sheds light on factors influencing the early initiation of breastfeeding and the practice of EBF as practiced in Polokwane.